Perceptions of nursing students on effective clinical preceptors in Phnom Penh National Hospitals, Cambodia - Koy, Virya (International Journal of Research in Medical Sciences, 2017)
Background:Nursing education has evolved substantially in the last few decades. Preceptorship is important to nursing education for several reasons. The purpose of this study is to describe the effective nursing clinical preceptors in Phnom Penh National Hospitals. Both preceptors and students have reported experiencing constrained relationships, tension and anxiety, which led to failure result or frustrating experiences in clinical teaching and learning. Methods: The stratified sampling of 166 was invited. A cross-sectional design survey was used. The Cronbach’s Alpha Coefficient for all items was 0.945. Results:The findings were given as effective clinical preceptorship had a moderate (3.02, 0.85). The interpersonal relationship (3.51, 0.88), evaluation (3.39, 0.93), personal traits (2.80, 0.83), nursing competencies (3.39, 0.93), and teaching ability (2.70, 0.81). Conclusion: Interpersonal relationship, formative evaluation, giving suggestions and correcting mistakes without belittling was perceived to be important characteristic. It is necessary to integrate clinical teaching skills to clinical preceptors.